Uno stato d'animo - Renato, Bordone (Reti Medievali E-Book, 2002)
City life in the Italy of the communes was a unique experience in the Middle Ages, "another world" from that of the countryside in terms of the customs, beliefs and practices that conditioned the attitudes of a complex society. In order to verify Lopez' definition of the city as a "frame of mind", the issues addressed include the perception and memory of time (both real and mythical), the elaboration of models of behaviour (that of chivalry), and the conditioning of the urban ambience through to the creation of an "acoustic landscape" of the city. The significance of what it meant to be a citizen in mediaeval Italy emerges tangibly from the evidence of contemporaries.